From strategic narrative to strategic culture: Labor Zionism and the roots of Israeli strategic culture. Issue 2 (3rd March 2020) - Ben-Ephraim, Shaiel
Abstract: Israeli strategic culture is offensive and militaristic. However, in the pre-state period the Labor Zionist elites which later dominated the Israeli security establishment formulated a security narrative trumpeting a defensive and antimilitaristic approach. This article explains that its security policy was designed to perpetuate domestic political hegemony. Since the Jewish people had not developed an approach to the use of force in centuries, the formulation of Labor Zionist approaches to security allows an insight into the process by which security narratives are initially derived and the process by they may (or may not) become a reified strategic culture.